Tale of two zones: investigating the clinical outcomes and research gaps in peripheral and transition zone prostate cancer through a systematic review and meta-analysis - Pedro Oliveira; Robert G Bristow; Ananya Choudhury; Ashwin Sachdeva; Noel Clarke; Hitesh Mistry; Amin Ali; Thiraviyam Elumalai; BhanuPrasad Venkatesulu; Lauren Hekman; Esther Baena (BMJ Oncology)
Objective To assess pathological characteristics, clinical features and outcomes of patients diagnosed with peripheral zone (PZ) and transition zone (TZ) prostate cancer after prostatectomy.Methods and analysis We systematically reviewed PubMed, EMBASE and MEDLINE. Primary endpoints were biochemical relapse-free survival (bRFS) and distant metastases rate; secondary endpoints included clinical and pathological features.Results Ten retrospective cohort studies were identified, six reported HRs for bRFS between PZ and TZ tumours. Patients with TZ tumours had significantly better bRFS (pooled HR 0.57 (0.47, 0.68)) than those with PZ tumours. Two studies reported a lower proportion of distant metastasis in patients diagnosed with TZ tumours compared with PZ tumours (1.5% vs 4.9% (median follow-up 7.0 years) and 0% vs 5% (median follow-up 7.8 years)). PZ tumours presented higher Gleason group and T staging more frequently, while TZ tumours were associated with higher prostate specific antigen levels at diagnosis.Conclusion PZ tumours were associated with poorer prognostic clinical features and outcomes. Despite adjusting for poor prognostic clinical features, PZ tumours consistently showed worse clinical outcomes than TZ tumours. Our systematic review underscores the need for further research comparing PZ and TZ prostate cancer to understand the underlying differences and refine clinical practice.